2020
DOI: 10.1016/j.jeurceramsoc.2020.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Micro-structural study of Yaozhou celadons (Tang to Yuan Dynasty): probing crystalline and glassy phases

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Magnetite clusters were also reported in the glaze of a brown Ding ware deep under layers containing only ε-Fe 2 O 3 [15]. Two broad peaks are also present at c. 500 and 1000 cm -1 which could be explained with the bending and stretching modes of the [SiO 4 ] ntetrahedron of the glassy matrix [19]. Fig.…”
Section: Figure 5 Raman Spectra Recorded In Glaze Surfaces Of the Four Samples ((A) Zircon (B) ε-Fe2o3 (C) Magnesioferrite (D) Hematite (mentioning
confidence: 73%
See 1 more Smart Citation
“…Magnetite clusters were also reported in the glaze of a brown Ding ware deep under layers containing only ε-Fe 2 O 3 [15]. Two broad peaks are also present at c. 500 and 1000 cm -1 which could be explained with the bending and stretching modes of the [SiO 4 ] ntetrahedron of the glassy matrix [19]. Fig.…”
Section: Figure 5 Raman Spectra Recorded In Glaze Surfaces Of the Four Samples ((A) Zircon (B) ε-Fe2o3 (C) Magnesioferrite (D) Hematite (mentioning
confidence: 73%
“…In order to investigate the depth of the glaze, cross-sections of each fragment was made following the preparation method described in detail in reference [19].…”
Section: Sample Descriptionsmentioning
confidence: 99%
“…The B5-B9 samples display two similar broad bands positioning at approximately 500 and 1,000 cm À1 , corresponding with the [SiO 4 ] nÀ tetrahedron bending and stretching modes, respectively. [20][21][22][23][24][25]37] It identified that the intensity of bending vibration mode decreased with increasing firing temperatures from 1,100 C (B5) to 1,300 C (B9), whereas that of stretching vibration mode increased accordingly. Besides, the peak position of the [SiO 4 ] nÀ stretching vibration mode moved towards the higher wavenumber.…”
Section: Phase Analysesmentioning
confidence: 99%
“…Raman spectroscopy, a nondestructive technique, is able to research the nature of vitreous glazes. [17][18][19][20][21][22][23][24][25][26][27] The glass network structure is composed of [SiO 4 ] 4À tetrahedral structure units containing different amounts of bridging oxygen. They are covalent and can exhibit remarkable Raman characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation